The Effect of Ultrasonication and Delignification Treatment on the Sugar Released Value of Wood - Wahyuni, Ika; Adi, Danang Sudarwoko; Risanto, Lucky; Fitria, Fitria; Dwianto, Wahyu; Hartati, Sri; Kaida, Rumi; Hayashi, Takahisa (Masyarakat Peneliti Kayu Indonesia, 2014)
The objective of these research was to study the impact of ultrasonication and delignification pretreatments in several wood species on their easiness for enzymatic hydrolysis, having the potential to be developed as the feedstocks for bioethanol production. Four different wood species from three botanical gardens in Indonesia have been selected, i.e., Gymnostoma sumatranum, Firmiana malayana, Pterocarpus indicus, and Alstonia scholaris, due to their higher sugar released values than a fast-grown tree, Sengon (Paraserianthes falcataria), when all were directly enzymatically hydrolyzed without pretreatment. The sugar released values after ultrasonication and enzymatic hydrolysis were between 3 – 5.5 mg/100 mg wood meal. When delignification pretreatment was performed, the sugar released values were higher than those with ultrasonication, ranging between 4 – 10.2 mg/100 mg wood meal. All the sugar released values after pretreatment were higher than those without pretreatment. Gymnostoma sumatranum was selected as the most potential wood species in this study due to its consistency among the species producing highest sugar released across different treatments. The SEM results showed that there was no significant changes in the morphological structure of the untreated fiber before and after enzymatic saccharification since it still had a complex structure due to the high lignin content. However, after the delignification treatment, the surface morphology of the fiber showed a decrease in the number of pits of the fiber, the surface residual of pits were reduced, parallel lines were more clearly visible, and the fiber structure was damaged with more small holes presented. The surface morphology of the fiber from the wood powder having delignification pretreatment supports the sugar released values which shows that the these values were higher than other treatments due to more recalcitrant substances were degraded, making it was easier for enzymes to break down cellulose. After ultrasonication, the SEM result showed less disrupted cell wall compared to after delignification which confirmed the higher sugar released data with delignification.